Long-term effect on foot and ankle donor site following vascularized fibular graft resection in children. Issue 5 (September 2015) - Sulaiman, Abdul Razak; Wan, Zulmi; Awang, Shukrimi; Che Ahmad, Aminudin; Halim, Ahmad Sukari; Ahmad Mohd Zain, Rajaei
Abstract : This study was carried out to evaluate the long-term effect on the donor side of the foot and ankle following vascularized fibular graft resection in children. Eight patients underwent resection of the fibula for the purpose of a vascularized fibular graft by a surgical team who practiced leaving at least 6 cm residual distal fibula. The age of these children at the time of surgery was between 3 and 12 years. They were reviewed between 3 and 12 years after surgery. Two patients who underwent resection of the middle shaft of the fibula at 3 and 5 years of age developed abnormal growth of the distal tibia, leading to ankle valgus. They were treated with growth modulation of the distal tibial physis and supramalleolar osteotomy with tibiofibular synostosis. Another patient who underwent the entire proximal fibula resection at the age of 6 years had developed hindfoot valgus because of weakness of the tibialis posterior muscle. He required talonavicular fusion and flexor hallucis to tibialis posterior muscle transfer. Patients operated at the age of older than 8 years neither had ankle nor hindfoot deformity. We concluded that resection of the middle shaft of the fibula for the purpose of a vascularized fibula graft, leaving a 6 cm distal fibular stump in children younger than 6 years old, may give rise to abnormal growth of the distal tibial physis, leading to valgus ankle. The entire proximal fibular resection for the similar purpose in a 6-year-old child may give rise to weakness of tibialis posterior and hindfoot valgus.